Od koncepta trajnosti k eko-socialnemu modelu tržnega gospodarstva in merjenje njegovega uresničevanja - Kovačič, Art (Naše gospodarstvo, 2006)
The EU countries have accepted the concept of sustainable development in their documents, including the strategic guidelines. Therefore, entrance to the EU is also dependent upon the implementation of the Lisbon Strategy of Competitiveness and the Goethenburg Strategy of Sustainable Development. Thus, Slovenia accepted the European acquis communautaire because it was a condition for entrance to the EU, and at the same time the country accepted higher cultural and environmental standards. In the article we try to apply the concept of sustainable development operative to an eco-social market economy model, which seems to be the most promising model in Europe and, we believe, the guarantee for achieving sustainability in Slovenia. For measuring its realisation, we propose the system of sustainable indicators.
Keywords: ekonomski razvoj; sustainable development; trajnostni razvoj; strategija; tržno gospodarstvo; konkurenčnost